PENGARUH AUDIT FEE,AUDIT TENURE,DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT - Zahra Ismi Fauziyyah; Praptiningsih Praptiningsih (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
This study was conducted to examine the effect of Audit Fee, Audit Tenure and Audit Rotation on Audit Quality on all financial companies listed in Indonesia Stock Exchange period 2015-2017. The sampling in this study of 38 financial companies listed in Indonesia Stock Exchange period 2015-2017 with purposive sampling method. Data obtained from the company’s financial statements that have been publication. The number of samples was obtained from 38 companies with total 114 sample.Quality audits in this study using a proxy public accounting firm size.The analysis technique that used in this study is logistic regression with a significance level of 5%. The results in this study indicates that (1) Audit Fee has significant positive effect on Audit Quality (2) Audit Tenure does not affect the Qualit of the audit, and (3) Audit Rotation does not affect the Quality of the Audit Keywords: Audit Fee, Audit Tenure , Audit Rotation , Audit Quality